Hydrothermal synthesis of WS2/RGO sheet and their application in UV photodetector - Shelke, Nitin T.; Karche, B. R. (Journal of Alloys and Compounds, 2015)
Two-dimensional (2D) semiconductor nanomaterials hold great promises for future electronics and optics. In this paper, we report UV photocurrent response of 2D hybrid materials consisting of layered WS2 nanosheets and reduced graphene oxide prepared by using one step hydrothermal method. Few-layer WS2 and WS2/RGO nanosheets are characterized by Raman spectroscopy and HRTEM. The electric and optoelectronic properties of WS2 and WS2/RGO based UV photodetector shows a fast response of 48s and 85s and high photosensitivity (80 mu AW(-1) and 3.21 mAW(-1)) indicating that the two-dimensional composite nanostructure WS2/RGO is an important material for high performance photodetectors. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: nanosheets; UV photodetector; WS2; WS2/RGO